Fluor Albus Characteristics Associated with Sexually Transmitted Infection (STI) in Makassar Pregnant Women - Haruna, Nadyah; Hatta, Mochammad; Hamid, Firdaus; Madjid, Baedah; Patellongi, Ilhamjaya; Farid, Monika Fitria (Al-Sihah: The Public Health Science Journal, 2023)
Sexually Transmitted Infection (STI) is a common condition with increased prevalence among pregnant women and can negatively affect the fetus. According to WHO, a total of 374 million new cases of STI are projected to occur in 2020, including gonorrhea (82 million), syphilis (7.1 million), and trichomoniasis (156 million). Therefore, this study aimed to determine the relationship between the characteristics of vaginal discharge (fluor albus) in pregnant women and STI. The descriptive method was used with a cross-sectional design, and the procedures were conducted in May 2023. The sample population comprised all pregnant women with ANC in Makassar during the study period. Vaginal swabs were obtained from 127 pregnant women who were willing to participate and had vaginal discharge. The results showed that 53 participants reported having physiological flour albus, while 74 had pathological symptoms. Itching and odor were reported to be the most common clinical signs associated with patients' abnormal vaginal discharge, followed by itching, pain, and odor. Furthermore, a significantly high prevalence of the condition was observed among pregnant women aged 20-30 years. Based on the results, the predominant symptom of fluor albus was itching and odor when combined with microorganisms that caused STI. Several pregnant women with clinical complaints also had microorganisms apart from those associated with STI. These results indicated the pressing need to develop additional testing in pregnant women with fluor albus, particularly those with concomitant symptoms.